Simulación con Monte Cario de la ordenación local y formación de agregados en una aleación modelo bidimensional - Rojas T, Justo (2002)
Using Monte Cario simulation have been carried out an.atomistic description of the structure and ordering processes in the system Cu - Au in a two-dimensional model. The ABV model of the alloy is a system of N atoms A and B, located in rigid lattice with sorne vacañt sites. In the model we assume pair wise interactions between nearest neighbors with constant ordering energy J,;, 0.03 eV. The dynarnics was introduced by means of a vacancy that exchanges of place with any atom of its neighbors . The simulations were carried out in a square lattice with 1024 and 4096 particles, using periodic boundary conditions to avoid border effects. We calculate the first two parameters of short range arder of Warren-Cowley as function of the concentration and tenl.petature. It was also studied the probabilities of formation of different atomic clusters that consist of 9 atoms as function of the concentration of the alloy and temperatures in a wide range of values. In sorne regions oftemperature and concentration it was observed compositional and thermal polymorphism. © 2001 CSI. Al! rights reserved